2018
DOI: 10.2147/ccide.s154641
|View full text |Cite
|
Sign up to set email alerts
|

Locating the second mesiobuccal canal in maxillary molars: challenges and solutions

Abstract: The second mesiobuccal canal in mesiobuccal roots in maxillary molars is a common finding in root canal treatments. Failure on the location of these canals is associated with a high rate of unsuccessful treatments of maxillary molars. Its prevalence has been assessed in several in vitro and in vivo studies, presenting variations according to the methodology applied, along with the population of interest. While the anatomy of these teeth is well defined in micro-computed tomography studies, the clinical managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 41 publications
0
20
0
8
Order By: Relevance
“…2 The presence of such root canals was first reported by Hess in 1925. 3 Christie WH (1991) and Fogel HM (2017) reported variation in distobuccal root canal and palatal canals of maxillary molars. 4,5 According to Witherspoon DE (2013), 44% of retreatment in maxillary first molars is due to missed canals and 93% of these missed canals are identified in the mesiobuccal-2 root canal.…”
Section: Introductionmentioning
confidence: 99%
“…2 The presence of such root canals was first reported by Hess in 1925. 3 Christie WH (1991) and Fogel HM (2017) reported variation in distobuccal root canal and palatal canals of maxillary molars. 4,5 According to Witherspoon DE (2013), 44% of retreatment in maxillary first molars is due to missed canals and 93% of these missed canals are identified in the mesiobuccal-2 root canal.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the maxillary molars, the MB2 canal's identification and clinical management are a great challenge for practitioners, and missing it may lead to unsuccessful endodontic treatments. 2,51 The present study identified a wide range of MB2 canal prevalence for both maxillary first (between 37.1% 25 and 88.5% 31 ) and second molars (between 21.8% 26 and 83.4% 31 ). Generally, there is a tendency for lower percentages of MB2 canals in maxillary second molars than in first molars, 5,8,52,53 but that condition was not markedly evident in the present review.…”
Section: Article In Pressmentioning
confidence: 55%
“…The use of a dental operating microscope and ultrasonic tips are highly recommended to effectively address this high prevalent MB2 root canal, mainly in cases where its orifice opening in the pulp chamber floor is not evident. 51,54 As for the mandibular molars in the Brazilian population, the two-rooted configuration with two root canals in the mesial root and a single canal in the distal root was the most common morphology in the present review. The most common root canal classifications in the mandibular first molar's mesial roots were Vertucci's Types II and IV, with the root canal orifice openings generally perceptible in the pulp chamber floor.…”
Section: Article In Pressmentioning
confidence: 81%
“…Proses sonikasi diterapkan dalam farmasi, makanan, kosmetik, air, pelapis, tinta, cat, pengerjaan logam, perawatan kayu, pengerjaan logam(37), nanokomposit, pestisida, bahan bakar, produk kayu dan banyak industri lainnya. Sonikasi juga dapat digunakan untuk mempercepat pembubaran, dengan cara memecah interaksi antarmolekul serta menganalisis dinamika molekular dan kinetika reaksi pada pembelahan molekul (38).Ini sangat berguna ketika tidak memungkinkan untuk mengaduk sampel, seperti tabung NMRdan juga dapat digunakan sebagai penyedia energi (39) [19] , 2012-2016 oksidasi [20] 2017-2018 sonochemic al [21] , PCR [22] 2019> langsung (AS) [16] , Depolimerisasi [17] , Degradasi [18] , Tes triple negative praktis tidak termasuk PJI(64).…”
Section: Sonikasi Memiliki Banyak Efek Baik Kimia Maupun Fisikefek unclassified